Study and analysis of corrosion in sewage collectors - Aliyev Makhmud; Maxmudova Dildora; Gurinovich Anatolii; Tursunov Zarif; Mamadiyorov Sardor (E3S Web of Conferences)
The article discusses the sewage systems of the city of Kattakurgan, which have such shortcomings as the complete absence of wastewater treatment, while the discharge of untreated wastewater increases sanitary and environmental risks for surrounding areas, leading to air pollution and groundwater contamination. The lack of quality control of wastewater discharged from industrial enterprises into urban networks leads to blockages and, in some cases, the destruction of gravity collectors. It also examines the types of destruction of the concrete surface of sewage pipelines and ways to eliminate them. To increase the durability of the reinforced concrete lining, a wide range of technologies, materials (various mastics, paints, facing, lining materials, etc.) and methods can be applied. Gas dilution in collectors can be achieved through natural ventilation or by creating forced ventilation using fans or gradients.